Kecerdasan Visual-Spasial, Kemampuan Numerik, dan Prestasi Belajar Matematika - Maman Achdiyat; Rido Utomo (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2017)
This research uses survey method aimed to know the influence of visual-spatial intelligence and numerical ability on mathematics learning achievement, in class VIII students of PGRI Junior High School in Tenjolaya Subdistrict. Sampling technique with random sampling to 111 samples. The technique of collecting data 25-point test of visual-spatial intelligence and 30 items about numerical ability in multiple choice, while mathematics learning achievement data is taken from grade repetition value (UKK). Before performing the hypothesis test, the validity test item for visual-spatial intelligence test and numerical ability test were tested using biserial point correlation. The calculation result of normality of data using chi-square means otherwise. Testing of statistical hypothesis with t-test and F-test. The result of the research shows that there is a significant influence on visual-spatial intelligence and numerical ability together to the achievement of learning mathematics.